CO Multi-line Imaging of Nearby Galaxies (COMING). IX. 12CO(J = 2–1)/12CO(J = 1–0) line ratio on kiloparsec scales. (11th February 2021) - Yajima, Yoshiyuki; Sorai, Kazuo; Miyamoto, Yusuke; Muraoka, Kazuyuki; Kuno, Nario; Kaneko, Hiroyuki; Takeuchi, Tsutomu T; Yasuda, Atsushi; Tanaka, Takahiro; Morokuma-Matsui, Kana; Kobayashi, Masato I N
Abstract: While molecular gas mass is usually derived from 12 CO( J  = 1–0)—the most fundamental line for exploring molecular gas—it is often derived from 12 CO( J  = 2–1) assuming a constant 12 CO( J  = 2–1)$/$ 12 CO( J  = 1–0) line ratio ( R 2/1 ). We present variations of R 2/1 and effects of the assumption that R 2/1 is a constant in 24 nearby galaxies using 12 CO data obtained with the Nobeyama 45 m radio telescope and IRAM 30 m telescope. The median of R 2/1 for all galaxies is 0.61, and the weighted mean of R 2/1 by 12 CO( J  = 1–0) integrated intensity is 0.66 with a standard deviation of 0.19. The radial variation of R 2/1 shows that it is high (∼0.8) in the inner ∼1 kpc while its median in disks is nearly constant at 0.60 when all galaxies are compiled. In the case that the constant R 2/1 of 0.7 is adopted, we found that the total molecular gas mass derived from 12 CO( J  = 2–1) is underestimated/overestimated by ∼20%, and at most by 35%. The scatter of molecular gas surface density within each galaxy becomes larger by ∼30%, and at most by 120%. Indices of the spatially resolved Kennicutt–Schmidt relation by 12 CO( J  = 2–1) are underestimated by 10%–20%, at most 39%, in 17 out of 24 galaxies. R 2/1 has good positive correlations with star-formation rate and infrared color, and a negative correlation with molecular gas depletion time. There is a clear tendency of increasing R 2/1 with increasing kinetic temperature ( T kin ). Further, we found that not only T kin but also pressure of molecular gas is important in understanding variations of R 2/1 . Special considerations should be made when discussing molecular gas mass and molecular gas properties inferred from 12 CO( J  = 2–1) instead of 12 CO( J  = 1–0).